(untitled) (Fiep Bulletin - online, 2012)
Introduction: Cleaning workers are at high risk for developing health problems especially those related to the musculoskeletal system due to performance of repetitive movements and awkward postures. The labor gymnastics is a tool used to minimize the effects caused by work, providing an improved quality of life. Objective: This study aimed to analyze the effects of a labor gymnastics program in pain in professional cleaning of an institucion of higher education. The initial sample consisted of 20 janitors who worked at FAG, only six of these remained. Before starting the intervention of the labor gymnastics program, a questionnaire was prepared by the author based on questionnaires used by Lima (2008), to check the topography of the pain, while also evaluating the pain worsens and improves feel and how long pain. The labor gymnastics adopted was the compensatory type, which uses stretching exercises and massage, the program was applied for a month, twice a week, lasting 15 minutes. At the close of the exercise program, was applied a new questionnaire based according to Mendes and Leite (2008), to assess whether there was a reduction of pain. Results: It was observed that 84% of the janitors felt pain, and 14% did not feel. At the end of the program, was determined that there was a reduction in pain in all participants. Thus the labor gymnastics is an essential tool for professionals in the routine of work becomes stressful, where a great physical effort is submitted and when they make use of awkward positions, and possibly is able to assist in improving the quality of life of these workers .